From Collective Action to Economic Sustainability: A Case of Community Participation in Local Tourism Development - Muthahari, Nisrina (Universitas Mataram, 2024)
This study examines community participation and empowerment in managing Goa Pindul-based tourism in Bejiharjo, Gunungkidul, managed by BUMDes Maju Mandiri. Using a qualitative case study approach, the research explores empowerment structures, power distribution, and women's roles. Findings reveal that contractual participation leads to empowerment bias and power contestation among agencies. Effective empowerment requires equitable power distribution through deliberative leadership communication. Moreover, while women play significant roles, their involvement remains confined to supporting functions, reflecting gender bias in empowerment. The study emphasizes the need to improve inclusive and sustainable empowerment structures. Implications include revising village regulations, enhancing gender awareness, and strengthening community capacity to achieve sustainable community-based tourism.